Digital Transformation of Car Rental Services Using a Web Based Information System - Muhammad Muttaqin; Fachrid Wadly; Pipin Veranda (Yayasan Sinergi Multidimensi Kreatif, 2025)
The rapid development of information technology has encouraged many business sectors to adapt and utilize technology to improve operational efficiency, including in the car rental industry. This research aims to design and build a web-based car rental management information system that is able to help business processes such as vehicle data collection, customer management, bookings, and transaction reporting in a structured and integrated manner. The system development method used is the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The result of this research is a web-based information system that can be used by admins and users efficiently to carry out the car rental process, as well as produce accurate and real-time reports. With this system, it is hoped that data management will be easier, service to customers will be more optimal, and the decision-making process by the management will be more precise based on the available data. This system also supports the digitization of services, so that it can increase the competitiveness of the car rental business in the current technological era.